Divergent [videorecording (Blu-Ray)] - Burger, Neil; Woodley, Shailene; James, Theo, 1984-; Judd, Ashley; Roth, Veronica (Lionsgate, 2014)
In a society that has organized itself into five factions, a teenage girl learns that she is a Divergent, and when she chooses to join a warring faction she discovers that her personality type is seen as a danger to other factions.